Effects of a Superabsorbent Resin with Boron on Bacterial Diversity of Peat Substrate and Maize Straw. (18th September 2018) - Wang, Yuxin; Wang, Chaonan; Zhao, Yanan; Wang, Pingzhi
Abstract : As a chemical water-saving material, superabsorbent resin is often applied to improve soil physicochemical properties for the purpose of promoting crop growth. In this study, a new type of superabsorbent resin with boron (SARB) was used as a functional material mixed with peat substrate and maize straw in percentages (mass ratio) of 0.05%, 0.1%, 0.15%, and 0.2%, respectively, and high-throughput sequencing technology was used to test bacterial diversity, analyzing and exploring ecological safety of the superabsorbent resin with boron (SARB) in order to provide theoretical support for field applications. The research results show that the superabsorbent resin with boron (SARB) can promote bacterial community diversity in the maize straw. In ten treatments, Proteobacteria accounted for the absolute advantage of the bacterial population in the CT group and in the JG group. However, the superabsorbent resin with boron (SARB) synthesized in the laboratory cannot change the original structure of the bacterial community and has scarcely any toxic effect on the bacterial community in both peat substrate and maize straw, and, indeed, it has a strengthening effect on Proteobacteria and Actinobacteria and a weakening effect on Acidobacteria and Firmicutes to some extent.